THE MAIN TRENDS IN THE BORROWED CAPITAL FORMATION OF AIRLINES COMPANY IN UKRAINE - Bohushko, O. M. (Science and Transport Progress, 2009)
Tendencies of forming the debt capital of Ukraine airlines were analyzed in the article. The major sources of forming the debt capital in aviation were also covered.